The Impact Of Independent Smallholder Fresh Fruit Bunch Quality On Corporate Profit Through CPO Production - Dolly Juanito; Mhd Asaad; Rasidin Karo Karo (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose : This study aims to analyze the effect of Third-Party Fresh Fruit Bunch (FFB) Quality (X) on Company Profitability (Y) at PT Sinergi Perkebunan Nusantara, by specifically examining the role of Crude Palm Oil (CPO) Production Volume (Z) as a mediating variable. Methodology : The Method of this research employed quantitative by case study approach using secondary time-series data from 2021–2024, this research applies path analysis to test the proposed causal relationship model. Results : The results of the research indicate that Third-Party FFB Quality, particularly the quantity of supply dimension, has a significant and positive effect on CPO Production Volume. Increased purchase volumes effectively mitigate chronic idle capacity issues, while improvements in the intrinsic quality of FFB contribute to achieving a superior Oil Extraction Rate (OER). Furthermore, higher CPO Production Volume is proven to be a primary driver of Company Profitability through economies of scale, which substantially reduce the Cost of Goods Sold (COGS) and enhance revenue potential. Findings : These findings conclusively confirm the mediation hypothesis, whereby CPO Production Volume functions as a crucial causal bridge that transmits upstream supply chain advantages into superior corporate financial performance. Novelty: The Novelty of this research enriches the literature on operations management and production theory by providing empirical validation of the mediating mechanism of operational variables in linking raw material input quality to financial performance in industries characterized by high fixed-cost structures. Originality: The research managerial implications emphasize the urgency of shifting the paradigm from transactional relationships toward strategic partnerships with independent smallholder farmers. Conclusion: The implementation of quality-based incentive schemes and technical assistance programs is essential to ensure the sustainability of corporate profitability. Type of Paper : Research Article.